Assessment of epicardial fat volume and myocardial triglyceride content in severely obese subjects: relationship to metabolic profile, cardiac function and visceral fat - Gaborit, B; Kober, F; Jacquier, A; Moro, P J; Cuisset, T; Boullu, S; Dadoun, F; Alessi, M-C; Morange, P; Clément, K; Bernard, M; Dutour, A (International Journal of Obesity, 2012)
Objective: To assess epicardial fat volume (EFV), myocardial TG content (MTGC) and metabolic profile in severely obese patients, and to determine whether ectopic fat depots are linked to metabolic disorders or myocardial function. Research design and methods: Sixty-three subjects with normal LV function and no coronary artery disease, including 33 lean (BMI: 21.4±2.0 kg m −2 ) and 30 obese (BMI: 41.8±6 kg m −2 ) patients, underwent 3-T cardiovascular MRI, and anthropometric, biological and visceral abdominal fat (VAT) assessments. EFV was measured by short-axis slice imaging and myocardial (intra-myocellular) TG content was measured by proton magnetic resonance spectroscopy. Results: EFV and MTGC were positively correlated ( r =0.52, P <0.0001), and were both strongly correlated with age, BMI, waist circumference and VAT, but not with severity of obesity. EFV and MTGC were significantly higher in obese patients than in lean controls (141±18 versus 79±7 ml, P =0.0001; 1.0±0.1 versus 0.6±0.1%, P =0.01, respectively), but some differences were found between the two cardiac depots: EFV was higher in diabetic obese subjects as compared with that in non-diabetic obese subjects (213±34 versus 141±18 ml, P =0.03), and was correlated with parameters of glucose tolerance (fasting plasma glucose, insulin and HOMA-IR), whereas MTGC was not. EFV and MTGC were both associated with parameters of lipid profile or inflammation (TGs, CRP). Remarkably, this was VAT-dependent, as only VAT remained independently associated with metabolic parameters ( P <0.01). Concerning myocardial function, MTGC was the only parameter independently associated with stroke volume (β=−0.38, P =0.01), suggesting an impact of cardiac steatosis in cardiac function. Conclusions: These data show that VAT dominates the relationship between EFV, MTGC and metabolic measures, and uncover specific partitioning of cardiac ectopic lipid deposition.